Crafting experiential value via smartphone apps channel. Issue 5 (7th August 2017) - Rezaei, Sajad; Valaei, Naser
Abstract : Purpose: The purpose of this paper is to investigate the impact of post-usage usefulness (PUU), experiential value, and apps channel satisfaction on consumer continuance intention in using the smartphone apps retail channel for shopping activities. The study proposes that experiential value mediates both the relationship between PUU and apps channel satisfaction and the relationship between PUU and apps channel continuance intention. Design/methodology/approach: A total of 467 valid questionnaires were received from Malaysian experienced smartphone apps shoppers (minimum of six months experience) from pure play apps retailers to empirically test the model. For the assessment of the measurement model and structural relationships, partial least square path modelling approach was performed. Findings: The hypotheses testing imply that all direct hypotheses between latent constructs are supported. Experiential value partially mediates the relationship between PUU and apps channel satisfaction and the hypothesis on its mediation role on the relationship between PUU and apps channel continuance intention is rejected. Originality/value: Despite the rapid development of information technology, a few research uncovered how businesses can create value through smartphone apps channel. Rather than focussing exclusively on online retailing, physical stores and e-commerce in general as a retail distribution strategy, this study empirically uncovered that value creation process could be achieved through smartphone apps channel.